Big Data in the MENA Region: The Next Path Towards Socio-economic and Cultural Development - Allagui, Ilhem (2017)
As elsewhere, big data is perceived as central to the Middle East and North Africa (MENA) nations’ socio-economic and cultural development. The Gulf Cooperation Council (GCC) region, by virtue of its advanced information technology infrastructure, relevant knowledge economy policies and flexible free government and market orientations, stands at the forefront of MENA’s big data integration. This article discusses selected sectors in the GCC region that leverage the power of big data including the media business industries and the oil and gas industry. The authors argue that in addition to bolstering big data applications in the aforementioned sectors, MENA countries also need to ensure that those applications embrace other sectors like education, government services and cultural development. Yet, to be able to achieve those goals, the region needs to address numerous challenges pertaining to knowledge infrastructure, human capital, technology mindset and regulation.